2003
DOI: 10.1046/j.1440-1746.2003.03081.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Rome II criteria for functional gastrointestinal disorders by factor analysis of symptoms in Asian patient sample

Abstract: Factor analysis of symptoms from a sample of Asian patients with functional GI disorders partially supported the use of the Rome II classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 15 publications
1
57
1
2
Order By: Relevance
“…20 The Chinese version of ESS, modified Chinese version of the Rome II questionnaire (gastroduodenal, bowel, and biliary items only) and the Chinese version of Reflux Disease Questionnaire (RDQ) were applied to measure EDS, FGIDs, and GERD. 6,16,[21][22][23] The ESS is an 8-item, self-administered questionnaire covering eight situations commonly encountered in daily life. Each participant was instructed to answer how likely it is that he/she would fall asleep in different situations by giving a score ranging from 0 to 3.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The Chinese version of ESS, modified Chinese version of the Rome II questionnaire (gastroduodenal, bowel, and biliary items only) and the Chinese version of Reflux Disease Questionnaire (RDQ) were applied to measure EDS, FGIDs, and GERD. 6,16,[21][22][23] The ESS is an 8-item, self-administered questionnaire covering eight situations commonly encountered in daily life. Each participant was instructed to answer how likely it is that he/she would fall asleep in different situations by giving a score ranging from 0 to 3.…”
Section: Measurementsmentioning
confidence: 99%
“…Furthermore, global consensus-based definitions of FGIDs and GERD were used, and reliability and validation of Chinese version of ESS were confirmed. 6,22,46 However, this study was a cross-sectional study and these types of studies are insufficient in establishing cause-effect relationships. Also, the prevalence of EDS found in this study might be overestimated because the ESS is a subjective measuring method.…”
mentioning
confidence: 97%
“…18 and Taiwan 19 show a decreasing trend of FD with age. In this study, most of the patients were in 30-39 years age group (42.86 %) followed by 40-49 years (27.27 %).…”
Section: Britainmentioning
confidence: 88%
“…Though most population based studies showed that frequency of uninvestigated dyspepsia (UD) was not related to gender, several studies in different population have noted a consistent female predominance with dyspepsia. [18][19][20][21][22] Female gender was found to be the only independent risk factor of FD among 2865 Taiwanese health check attendees. 21 In one population based study in Australia, female adults significantly outnumbered males in most GI disorders including FD.…”
Section: 16mentioning
confidence: 99%
“…Tack et al have reported a higher frequency of epigastric pain in a subset of heartburn negative functional dyspepsia patients with pathological esophageal acid exposure (16). Epigastric pain together with nausea/vomiting, postprandial fullness or early satiation, comprise the different groups of symptoms in functional dyspepsia (17)(18)(19)(20). Hence, it is possible that the increased frequency of the first two symptoms in the IBS subjects compared to the controls in our study volunteers, is related to gastroesophageal reflux but we can not rule out that they may be a manifestation of a comorbidity with functional dyspepsia.…”
Section: Discussionmentioning
confidence: 99%